2023
DOI: 10.3390/cancers15061879
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Matrix in Glioblastomas: A Glance at Its Structural Modifications in Shaping the Tumoral Microenvironment—A Systematic Review

Abstract: Background and aim: While many components of the ECM have been isolated and characterized, its modifications in the specific setting of GBMs have only been recently explored in the literature. The aim of this paper is to provide a systematic review on the topic and to assess the ECM’s role in shaping tumoral development. Methods: An online literature search was launched on PubMed/Medline and Scopus using the research string “((Extracellular matrix OR ECM OR matrix receptor OR matrix proteome) AND (glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Tumor-instructed stromal cells have differential effects on tumor cell proliferation and migration in vitro, indicating a reciprocal crosstalk between neoplastic and non-neoplastic cells, such as EC (Bougnaud et al, 2016;Testa et al, 2022). The composition of ECM and its stored-signaling factors also influence the behavior of GBM cells and GBM stromal cells, affecting GBM angiogenesis, infiltration and aggressiveness (Alves et al, 2011a;Dinevska et al, 2023;Marino et al, 2023). Understanding the complex interplay between the ECM, GBM cells and EC in the tumor angiogenesis and aggressiveness is crucial for finding new biomarkers to improve patient outcomes and for the development of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-instructed stromal cells have differential effects on tumor cell proliferation and migration in vitro, indicating a reciprocal crosstalk between neoplastic and non-neoplastic cells, such as EC (Bougnaud et al, 2016;Testa et al, 2022). The composition of ECM and its stored-signaling factors also influence the behavior of GBM cells and GBM stromal cells, affecting GBM angiogenesis, infiltration and aggressiveness (Alves et al, 2011a;Dinevska et al, 2023;Marino et al, 2023). Understanding the complex interplay between the ECM, GBM cells and EC in the tumor angiogenesis and aggressiveness is crucial for finding new biomarkers to improve patient outcomes and for the development of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Although an early report mentioned a relationship between LAMC1 and hypoxia [33], this study clari ed the regulatory relationship between HIF-1α and LAMC1 expression, which expands our understanding of the molecular mechanism of ECM remodeling in the hypoxic microenvironment of malignant tumors. As a major factor involved in tumorigenesis, progression, and the tumor microenvironment, the ECM has become a therapeutic target and potential prognostic marker for gliomas [34]. By considering LAMC1 as target, Kulkarni et al found that LAMC1 and laminin family members are critical for H-1 parvovirus cell attachment and entry, and can be used as biomarkers to facilitate identifying sensitivity to H-1 parvovirus oncolytic therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…As a major factor involved in tumorigenesis, progression, and the tumor microenvironment, the ECM has become a therapeutic target and potential prognostic marker for gliomas [ 36 ]. By considering LAMC1 as target, Kulkarni et al found that LAMC1 and laminin family members are critical for H-1 parvovirus cell attachment and entry, and can be used as biomarkers to facilitate identifying sensitivity to H-1 parvovirus oncolytic therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%